Sustainability of breastfeeding interventions to reduce child mortality rates in low, middle-income countries: A systematic review of randomized controlled trials - Engelhart, Alexis; Mason, Stacey; Nwaozuru, Ucheoma; Obiezu-Umeh, Chisom; Carter, Victoria; Shato, Thembekile; Gbaja-Biamila, Titilola; Oladele, David; Iwelunmor, Juliet (Frontiers in Health Services, 2022)
Child mortality is the lowest it has ever been, but the burden of death in low- and middle-income countries (LMICs) is still prevalent, and the numbers average above the global mean. Breastfeeding contributes to the reduction of child mortality by improving chance of survival beyond childhood. Therefore, it is essential to examine how evidence-based breastfeeding interventions are being maintained in resource-constrained settings. Guided by Scheirer and Dearing's sustainability framework, the aim of this systematic review was to explore how evidence-based breastfeeding interventions implemented to address child mortality in LMICs are sustained. The literature search included randomized controlled trials (RCTs) of breastfeeding interventions from the following electronic databases: Cochrane Library, Global Health, PubMed, Scopus, and Web of Science. Literature selection and data extraction were completed according to the PRISMA guidelines. A narrative synthesis was used to investigate factors that contributed to sustainability failure or success. A total of 497 articles were identified through the database search. Only three papers were included in the review after the removal of duplicates and assessment for eligibility. The three RCTs included breastfeeding interventions predominately focusing on breastfeeding initiation and exclusivity in rural, semi-rural, and peri-urban areas in South Africa, Kenya, and India. The number of women included in the studies ranged from 901 to 3,890, and the duration of studies stretched from 6 weeks to 2.5 years. In two studies, sustainability was reported as the continuation of the intervention, and the other study outlined program dissemination and scale-up. Facilitators and barriers that influenced the sustainability of breastfeeding interventions were largely related to specific characteristics of the interventions (i.e., strong intervention implementers—facilitator; small number of CHWs involved—barrier). Optimizing the sustainability of breastfeeding interventions in LMICs is imperative to reduce child mortality. The focal point of implementation must be planning for sustainability to lead to continued benefits and changes in population outcomes. A defined action plan for sustainability needs to be included in both funding and research.